The etiology of primary pneumococcal peritonitis - McCartney, James Elvins (The University of Edinburgh, 1922)
The object of this Thesi3 is to show that Primary Pneumococcal Peritonitis is a disease that occurs only in female children, and that the infec¬ tion reaches the peritoneum by way of the genital tract.